Lung epithelium development and airway regeneration - Eenjes, Evelien; Tibboel, Dick; Wijnen, Rene M.H.; Rottier, Robbert J. (Frontiers in Cell and Developmental Biology, 2022)
The lung is composed of a highly branched airway structure, which humidifies and warms the inhaled air before entering the alveolar compartment. In the alveoli, a thin layer of epithelium is in close proximity with the capillary endothelium, allowing for an efficient exchange of oxygen and carbon dioxide. During development proliferation and differentiation of progenitor cells generates the lung architecture, and in the adult lung a proper function of progenitor cells is needed to regenerate after injury. Malfunctioning of progenitors during development results in various congenital lung disorders, such as Congenital Diaphragmatic Hernia (CDH) and Congenital Pulmonary Adenomatoid Malformation (CPAM). In addition, many premature neonates experience continuous insults on the lung caused by artificial ventilation and supplemental oxygen, which requires a highly controlled mechanism of airway repair. Malfunctioning of airway progenitors during regeneration can result in reduction of respiratory function or (chronic) airway diseases. Pathways that are active during development are frequently re-activated upon damage. Understanding the basic mechanisms of lung development and the behavior of progenitor cell in the ontogeny and regeneration of the lung may help to better understand the underlying cause of lung diseases, especially those occurring in prenatal development or in the immediate postnatal period of life. This review provides an overview of lung development and the cell types involved in repair of lung damage with a focus on the airway.